2019
DOI: 10.1371/journal.pone.0215814
|View full text |Cite
|
Sign up to set email alerts
|

Low altitude simulation without hypoxia improves left ventricular function after myocardial infarction by reducing ventricular afterload

Abstract: Humans have a lower risk of death from myocardial infarction (MI) living at low elevations (<2500 m), which are not high enough to induce hypoxia. Both chronic hypoxia pre-MI, achieved by altitude simulation >5000 m, and intermittent hypobaric hypoxia post-MI can reduce MI size in rodents, and it is believed that hypoxia is the key stimulus. To explore mechanisms beyond hypoxia we studied whether altitude simulation <2500 m would also be associated with reduced infarct size. We performed left-anterior descendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The main function of the heart in the circulatory system is to pump blood to meet the needs of metabolism. Thus, SV is also a basic indicator used to evaluate cardiac function [ 22 ]. Our present results demonstrated that treatment with SA preserved cardiac function and improved cardiac tissue damage and fibrosis in mice subjected to AMI injury.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of the heart in the circulatory system is to pump blood to meet the needs of metabolism. Thus, SV is also a basic indicator used to evaluate cardiac function [ 22 ]. Our present results demonstrated that treatment with SA preserved cardiac function and improved cardiac tissue damage and fibrosis in mice subjected to AMI injury.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased expression of HIF1α in the calf tissue of treatment mice after exposure to low altitude shows that the benefit of the treatment is not due to a downstream effect of hypoxia. We have previously shown a similar therapeutic benefit in a mouse model of MI (Shahid et al, 2019) and believe a mechanical mechanism where reductions in barometric pressure reduce the external compressive forces on arteries, thereby improving vessel dilation and blood flow to ischemic areas is likely ( Figure 6).…”
Section: Discussionmentioning
confidence: 65%
“…Immediately after the surgery was completed, animals in the experimental group were placed in an altitude simulation chamber with a barometric pressure of 714 mmHg for a period of 3 hours to simulate low altitude before continuing recovery at room barometric pressure. We have previously shown small reductions in barometric pressure to have an acute and immediate effect on vascular function ex vivo and cardiovascular hemodynamics in vivo and we chose treatment with 714 mmHg at 3 h daily in light of our previous work (Shahid et al, 2016, 2019; Shahid, Patel, et al, 2016). As the animals did not have access to food and water inside the altitude simulation chamber due to space limitations, three hours was deemed to be the maximum amount of time the animals could ethically be kept in the chamber by the Animal Care and Use Committee at the University of Alberta.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations